Failure analysis of a superheater tube of a coal-fired power plant - Reis Piedade, Salustiano Dos (2008)
Failure analysis of structures has gained a considerable interest in many engineering areas. The aim of this research is to determine the root cause of the structural failures which can reduce the failure risks and prevent similar failures in the future. This thesis presents experimental investigations for the failure of a superheater tube of a coal-fired power plant using several failure analysis procedures. The failure analysis comprised of visual inspection, optical microscopic, scanning electron microscopy combined with the energy dispersive X-ray spectroscopy (EDS) and energy dispersive X-ray diffraction (EDXD). A sample of a total-fractured superheater tube obtained from an industry was used in this investigation. Initial visual investigations found that the superheater tube had a longitudinal crack. This fracture appearance is called fish mouth stress rupture. The specimen was initially cut, mounted, grinded, polished and etched. A significant oxide layer of 1.75mm in thickness was occurred in the steam side surface. The optical microscopy and scanning electron microscopy were used to identify intergranular cracks, voids, elongated grain and deposit layers. The EDS and EDXD were used to identify types and compositions of the oxide substances. The results revealed that the steam and fire side surfaces consist of sodium iron oxide, hematite and magnetite. The study also demonstrates that the superheater tube of a coal-fired failed due to creep mechanism. This resulted inoverheating problem inside the tube; caused by deposit layers, which contributes to the creep mechanism. Periodically cleaning and maintenance should be done in order to avoid accumulation of deposit layers.